Compliance of Sharia Audit in Islamic Banks and Islamic Financial Institutions in Palestine: A Literature Review - Faza', Mustafa; Badwan, Nemer (Journal of Islamic Economics and Finance Studies, 2024)
Sharia audits are required to make sure that Islamic financial institutions adhere to Islamic sharia standards in their financial and operational activities, and that the goods and services they provide to international financial institutions do not contravene any Islamic laws. This study aims to accomplish its objectives and provide answers to its questions. To accomplish the primary objective of this research, a systematic literature review, content analysis, and descriptive techniques were employed. This study used a systematic literature review methodology to locate, evaluate, and consolidate the extant literature on the analytical topic. This study analyses the differences in the roles of internal and external auditors between (IFIs) and (IBs) while considering the subject matter of internal sharia audits and the credentials of sharia auditors. This analysis is conducted through a literature review and examination of the existing literature on sharia audit compliance and governance. Consequently, the advantages of sharia compliance audits will be increased, and upcoming legal amendments will be put in place to minimize or eliminate the danger of sharia's noncompliance. This study provides a literature review and a theoretical and conceptual understanding of sharia audit compliance in Islamic financial institutions and banks. This study proposes a theoretical framework to evaluate the importance of sharia audit governance and identifies the basic elements that affect compliance, quality, and effectiveness in Islamic banks and financial institutions in Palestine. Compliance with the Islamic sharia audit can lead to optimal benefits, and future legislative changes can be implemented to minimize or eliminate the dangers of non-compliance with sharia.